ELECTRIC AND PLUG‐IN HYBRID VEHICLE DEMAND: LESSONS FOR AN EMERGING MARKET. (10th November 2016) - Sheldon, Tamara L.; DeShazo, J. R.; Carson, Richard T.
Abstract : Understanding demand in the new plug‐in hybrid electric vehicle (PHEV) market is critical to designing more effective adoption policies. We use stated preference data from an innovative choice experiment to estimate demand for PHEVs relative to battery electric vehicles (BEVs) and to explore heterogeneity in demand for these vehicles. We find the gap between willingness to pay for PHEVs and their price premium over conventional vehicles is on the order of current subsidies, while that of BEVs is an order of magnitude larger. We use a latent class model to show PHEVs draw a different consumer segment into the market. ( JEL Q5, R41)